2021
DOI: 10.1186/s13104-021-05699-1
|View full text |Cite
|
Sign up to set email alerts
|

High carbohydrate intakes may predict more inflammatory status than high fat intakes in pre-menopause women with overweight or obesity: a cross-sectional study

Abstract: Objective The associations between dietary carbohydrate, fat intake, and inflammation are controversial. Most existing data are from industrialized societies which low-carbohydrate and high-fat diet is common and so their attribution to other populations remains unclear. We evaluated the association of fat and carbohydrate intakes with inflammatory markers in pre-menopause women with overweight or obesity in Iran. Results Three hundred and sixty wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(52 reference statements)
0
7
0
1
Order By: Relevance
“…We and others previously demonstrated that under pathological conditions, high-carbohydrate RD promotes inflammation [ 38 , 39 , 40 , 41 ]. In addition, it has been shown that the pro-inflammatory transcription factor NF-κB plays a crucial role in the metabolic profile of pediatric sarcomas, potentially through the regulation of glycolysis (HK2) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We and others previously demonstrated that under pathological conditions, high-carbohydrate RD promotes inflammation [ 38 , 39 , 40 , 41 ]. In addition, it has been shown that the pro-inflammatory transcription factor NF-κB plays a crucial role in the metabolic profile of pediatric sarcomas, potentially through the regulation of glycolysis (HK2) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have revealed that high dietary cholesterol leads to increased adipocyte size, expression of pro-inflammatory cytokines, and macrophage infiltration (72,73). Karimi et al reported that high carbohydrate intake had a positive association with monocyte chemoattractant protein-1 (MCP-1) and transforming growth factor beta (TGF-β) that were related to increased expression of NF-κB as the main regulator of pro-inflammatory cytokine expression (74).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed that the association of Lactococcus and carbohydrate linked to the higher symptoms of depression. Recent studies have suggested that high carbohydrate consumption is associated with increased circulating inflammatory markers (Karimi et al, 2021). Mice fed with carbohydrate-enriched diet showed higher levels of obesity, which may also facilitate the development of depressive-like behaviors after the stress (Santos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%